2011
DOI: 10.1097/dbp.0b013e3181f51907
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Issues in Children and Adolescents With HIV Infection Evaluated With a World Health Organization Age-Specific Descriptor System

Abstract: Psychosocial issues are part of the well-being of children with HIV. The ICF is a standard tool to evaluate the clinical and psychosocial status of children and adolescents with HIV infection and to measure the impact of therapeutic interventions and strategies on psychosocial functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…A cohort study of perinatally infected children and adolescents on ART in the United States found that depression or anxiety was predictive of non-adherence [ 16 ]. Meanwhile, on the environmental level, stigma [ 14 ], social or familial support [ 17 ] and socioeconomic status [ 15 ] can impact usage of healthcare services by youth and adolescents. People belonging to YKP can be stigmatized for their engagement in risk behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study of perinatally infected children and adolescents on ART in the United States found that depression or anxiety was predictive of non-adherence [ 16 ]. Meanwhile, on the environmental level, stigma [ 14 ], social or familial support [ 17 ] and socioeconomic status [ 15 ] can impact usage of healthcare services by youth and adolescents. People belonging to YKP can be stigmatized for their engagement in risk behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…7 Interestingly, the greatest impairment reported by parents was related to the need of hiding the HIV infection status to their children because of social stigma. This was associated with delayed disclosure, 7 which in turn generated a vicious cycle of increased anxiety, ultimately leading to further functional disabilities in HIV-infected children. Therefore, disclosure has a key role in coping with HIV infection.…”
mentioning
confidence: 99%
“…In children and adolescents, ART is effective in controlling HIV-related symptoms; but the overall quality of life is far from optimal, owing to problems in the psychosocial sphere (10). In a previous study, we observed a major burden of psychosocial issues in a population of HIV-infected compared to a population of non-HIV-infected children (20). Poor socioeconomic conditions, high rates of unemployment, family breakdown, and problems in HIV disclosure are the most difficult obstacles in the management of HIV-infected adolescents (21).…”
Section: Discussionmentioning
confidence: 79%